2023
DOI: 10.1007/s11606-023-08137-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Cigarettes: an Overlooked Tool to Alleviate Disparities in Tobacco Use Disorder Among People with Mental Health and Substance Use Disorders

Abstract: The remarkable decline in cigarette smoking since 1964 has plateaued; approximately 12.5% of Americans still smoke. People who continue to smoke are largely members of marginalized groups, such as people with behavioral health conditions (BHC), encompassing both mental health and substance use disorders. Certified smoking cessation interventions can increase smoking abstinence in trials in people with BHC, yet smoking rates remain markedly increased, leading to increased mortality from smoking-related diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Within the PLWH study group, we recognized two distinct populations: PLWH who were currently using recreational drugs as evidenced by self‐report and confirmed by urine toxicology screen, and PLWH who were not. Initially we considered excluding PLWH who had a positive toxicology screen, but we realized that by doing so we would be excluding a group chronically understudied, those with behavioral health conditions, who also carry the heaviest smoking burden (Vuong et al., 2023 ). In our post‐hoc analysis of these subgroups, we found that at baseline, demographics were not different between the PLWH‐Drug and PLWH‐No Drug subgroups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the PLWH study group, we recognized two distinct populations: PLWH who were currently using recreational drugs as evidenced by self‐report and confirmed by urine toxicology screen, and PLWH who were not. Initially we considered excluding PLWH who had a positive toxicology screen, but we realized that by doing so we would be excluding a group chronically understudied, those with behavioral health conditions, who also carry the heaviest smoking burden (Vuong et al., 2023 ). In our post‐hoc analysis of these subgroups, we found that at baseline, demographics were not different between the PLWH‐Drug and PLWH‐No Drug subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Switching to electronic cigarettes (ECs), which deliver comparable levels of nicotine accompanied by lower levels of non‐nicotine toxicants and carcinogens compared to combusted TCs, has been proposed as a harm reduction approach in vulnerable populations with high smoking prevalence, such as PLWH, who are unable or unwilling to stop smoking (Cioe et al., 2020 ; Vuong et al., 2023 ). It is important to examine the evidence that forms the foundation of this harm reduction proposal, that is, that ECs, while not harmless, are less harmful than TCs.…”
Section: Introductionmentioning
confidence: 99%